2018
DOI: 10.1007/s13178-018-0339-8
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Sex Workers Weigh the Costs and Benefits of Disclosing Their Occupational Status to Health Providers

Abstract: Prostitution stigma has been shown to negatively affect the work, personal lives, and health of sex workers. Research also shows that sex workers have much higher unmet health care needs than the general population. Less is known about how stigma obstructs their health-seeking behaviors. For our thematic analysis, we explored Canadian sex workers' accounts (N = 218) of accessing health care services for work-related health concerns. Results show that participants had mixed feelings about revealing their work s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…Our results also align with prior research identifying provider stigma associated with sex work as a primary barrier to health care access for this population. 3 , 4 , 22 Our finding that many young adult sex workers reported that they chose not to disclose their sex work involvement to health care providers is also consistent with previous studies, 4 , 23 in particular literature indicating that sex workers with additional stigmatizing identities (in this case, youth) were particularly unlikely to disclose. 23 Given that prior research has established long-term impacts of negative experiences with health care on sex workers’ future decisions to seek care when needed, 4 these experiences of young adult sex workers may have lasting health impacts well into adulthood.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results also align with prior research identifying provider stigma associated with sex work as a primary barrier to health care access for this population. 3 , 4 , 22 Our finding that many young adult sex workers reported that they chose not to disclose their sex work involvement to health care providers is also consistent with previous studies, 4 , 23 in particular literature indicating that sex workers with additional stigmatizing identities (in this case, youth) were particularly unlikely to disclose. 23 Given that prior research has established long-term impacts of negative experiences with health care on sex workers’ future decisions to seek care when needed, 4 these experiences of young adult sex workers may have lasting health impacts well into adulthood.…”
Section: Discussionsupporting
confidence: 89%
“…Given that our study identified involvement of people with sex work experience as a primary facilitator of health care access, involving the sex work community in the development and delivery of these interventions will be important. The finding that many young adult sex workers reported that they chose not to disclose their involvement in sex work to their provider also has concerning implications for the quality of care they are likely to receive: Benoit and colleagues 23 found that sex workers were more likely to experience benefits than harms of sex work disclosure. Thus, for organizations that have developed capacity to provide competent care to sex workers, community outreach efforts to encourage disclosure may be warranted.…”
Section: Researchmentioning
confidence: 99%
“…Given the correlation existing between chlamydia/ gonorrhea testing and HIV/syphilis testing, integrating chlamydia and gonorrhea testing into the wellestablished HIV or syphilis testing programs has the potential to increase test uptake among FSW. Besides, reducing stigma from health care providers [31][32][33] and increasing social support from intimate partners [34] can promote chlamydia and gonorrhea testing among FSW. Our data showed that most of FSW were immigrants (77.6%).…”
Section: Discussionmentioning
confidence: 99%
“…prescription of female hormones) (Padilla et al, 2016). Yet, as other authors (Benoit et al, 2019) argue, the interaction with health providers was described by our participants as comfortable, nonjudgmental and supportive; even though they did not disclose their occupation as sex workers to their GP (Bungay et al, 2013). They thought it was no need for the GP to know their occupation, and conversely, they felt more appropriate to disclose this information in the sexual clinics when they request STI-HIV screening, condoms and lubricants because of their job.…”
Section: Discussionmentioning
confidence: 53%